Who i am ebook A memoir. - Townshend, Pete (2023)
The English musician and member of the rock band The Who shares stories from his career in this New York Times –bestselling memoir. One of rock music's most intelligent and literary performers, Pete Townshend—guitarist, songwriter, editor—tells his closest-held stories about the origins of the preeminent twentieth-century band The Who, his own career as an artist and performer, and his restless life in and out of the public eye in this candid autobiography,  Who I Am . With eloquence, fierce intelligence, and brutal honesty, Townshend has written a deeply personal book that also stands as a primary source for popular music's greatest epoch. Readers will be confronted by a man laying bare who he is, an artist who has asked for nearly sixty years: Who are you? Praise for Who I Am "Raw and unsparing...as intimate and as painful as a therapy session, while chronicling the history of the band as it took shape in the Mod scene in 1960s London and became the very embodiment of adolescent rebellion and loud, anarchic rock 'n' roll." —Michiko Kakutani, New York Times "Intensely intimate . . . candid to the point of self-laceration . . . [Townshend's] tone is less lofty than anyone would have expected, just as this book is more honest than any fan would have hoped." — Rolling Stone  (Four 1/2 Stars) "Unusually frank and moving . . . [ Who I Am ] isn't one of those rock memoirs that puts the what before the why. His past is a puzzle Mr. Townshend is sweating to decipher." — The Guardian  (UK)